Implementasi Kebijakan Pembangunan Pelabuhan Menjadi Objek Wisata pada Pelabuhan Marina Muaro Padang Kota Padang - Handika, Farel; Adnan, Fachri (Policy, Law and Political Research Center, 2023)
This research is motivated by the lack of optimal implementation of port development into a tourist attraction at Muaro Padang Marina Port, Padang City. This research was conducted using a qualitative approach with a descriptive method. The research location was carried out at the Tourism Office of West Sumatra Province. In determining informants, researchers use purposive sampling methods and techniques. In this study using data types, namely primary data and secondary data. Data collection techniques are carried out by interviews, observation, and documentation. In testing the validity of the data, researchers used method triangulation techniques. As for data analysis techniques using data reduction, data presentation, and conclusions. The results showed that socialization efforts have been carried out regularly and also consistently by the West Sumatra Provincial Government through the Development Cooperation Bureau of the West Sumatra Provincial Government and the West Sumatra Provincial Tourism Office, together with PT Pelindo II, this was discussed through regular meetings. Workplace resources are relatively adequate, but policy implementation has not been well implemented. Disposition, viewed as derived from expectations or behavior derived from employee policy implementers is not a sign of a supportive behavior to support policy implementation, this can be seen the implementation of the Port Development Policy on Marina Center Port Tourism in terms of Disposition has not been expected optimally, so cooperation or mutual assistance is needed to take a firm stance in the implementation of the Port Development Policy on Port Tourism Marina Center.